Cutaneous and Pulmonary Tuberculosis—Diagnostic and Therapeutic Difficulties in a Patient with Autoimmunity - Monika Kozińska; Ewa Augustynowicz-Kopeć; Andrzej Gamian; Anna Chudzik; Mariola Paściak; Przemysław Zdziarski (Pathogens, 2023)
Cutaneous tuberculosis (CTB) is a very rare disease and accounts for only 1–2% of cases of extrapulmonary tuberculosis (EPTB). Due to the variety of its clinical manifestations, the uncharacteristic appearance of its lesions, resembling other dermatoses in the early stages, and the limited experience of clinicians due to the rarity of CTB, diagnosis is very difficult. Particularly noteworthy is the fact that most cases of EPTB, including skin tuberculosis (TB), can be a manifestation of systemic involvement. In this paper, we present a case of an immunocompromised patient who was diagnosed with CTB almost a year after the first dermatological lesions were located on the lower extremities. At the same time, due to respiratory symptoms, a diagnosis of pulmonary TB (PTB) was made, and radiological and microbiological confirmations were obtained.